2018
DOI: 10.1021/acs.bioconjchem.8b00541
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Labeling and Affinity Capture of Inosine-Containing RNAs Using Acrylamidofluorescein

Abstract: Adenosine-to-inosine (A-to-I) RNA editing is a widespread and conserved post-transcriptional modification, producing significant changes in cellular function and behavior. Accurately identifying, detecting, and quantifying these sites in the transcriptome is necessary to improve our understanding of editing dynamics, its broader biological roles, and connections with diseases. Chemical labeling of edited bases coupled with affinity enrichment has enabled improved characterization of several forms of RNA editin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 25 publications
1
29
0
Order By: Relevance
“…In assembling reaction mixtures, we also noted improved solubility of EPhAA compared to acrylamidofluorescein, and we were able to double our normal working concentrations to ≈500 m m . As expected, this resulted in more rapid overall reaction kinetics, and when compared to our previous reagent, we observed a ≈2–3‐fold increase in conversion percentages at similar reaction times (Figure d) . Next, we incubated EPhAA with the remaining ribonucleosides uridine (U), guanosine (G), adenosine (A), and cytidine (C) (Figures d, S6).…”
Section: Methodssupporting
confidence: 70%
See 1 more Smart Citation
“…In assembling reaction mixtures, we also noted improved solubility of EPhAA compared to acrylamidofluorescein, and we were able to double our normal working concentrations to ≈500 m m . As expected, this resulted in more rapid overall reaction kinetics, and when compared to our previous reagent, we observed a ≈2–3‐fold increase in conversion percentages at similar reaction times (Figure d) . Next, we incubated EPhAA with the remaining ribonucleosides uridine (U), guanosine (G), adenosine (A), and cytidine (C) (Figures d, S6).…”
Section: Methodssupporting
confidence: 70%
“…While acrylonitrile is a promising scaffold for chemical detection of inosine, derivatizing these reagents is difficult and requires several synthetic and purification steps. Alternatively, we recently reported an acrylamidofluorescein reagent that enables fluorescent detection and enrichment of inosine in RNA . While our initial study demonstrated feasibility, acrylamidofluorescein also displayed poor solubility and was restricted to fluorescein addition.…”
Section: Methodsmentioning
confidence: 90%
“…Another inosine labeling approach uses bulky acrylamidofluorescein for selective N1-inosine derivatization. Such labeling does not require subsequent reactions for affinity capture with specific antibodies and it can be used for the comprehensive transcriptome-wide analysis of A-to-I editing [ 43 ].…”
Section: Analysis Of Rna Modifications By Ngsmentioning
confidence: 99%
“…It has been known for several decades that Michael acceptors, in particular acrylonitrile, can react with N 1 on inosine to form a stable adduct on the Watson‐Crick‐Franklin face (Yoshida & Ukita, 1965). We and others have applied this chemistry toward the design of inosine‐enrichment reagents; however, these compounds also reacted with pseudouridine and uridine, which overall limited their enrichment potential (Knutson, Ayele, & Heemstra, 2018; Li, Göhl, Ke, Vanderwal, & Spitale, 2019). In search of improved methods to address this enrichment problem we were inspired by Endonuclease V (EndoV), an evolutionary conserved repair enzyme that recognizes and cleaves inosine in nucleic acids.…”
Section: Commentarymentioning
confidence: 99%